Cerebral arterial and venous thrombosis due to COVID-19 vaccine-induced immune thrombotic thrombocytopenia. Issue 1 (18th January 2022) - Pang, Elaine; Ghosh, Soumya; Chemmanam, Thomas; Grove, Carolyn; Phillips, Tim
Abstract : Vaccine-induced immune thrombotic thrombocytopenia (VITT) rarely develops after many COVID-19 vaccines. A 51-year-old woman re-presented to hospital with a 4 day history of headache, vomiting, diarrhoea and left calf pain, 11 days after her first dose of ChAdOx1nCoV-19 (AstraZenica) vaccine. Her neurological examination was normal. Blood tests demonstrated a low platelet count, raised D-dimer and CRP, and a positive heparin/anti-PF4 antibody assay. CT venogram demonstrated widespread cerebral venous sinus thrombosis. She was commenced on fondaparinux and intravenous immunoglobulins. The following day she developed an asymmetric quadriplegia and aphasia. CT angiogram demonstrated new bilateral cervical internal carotid artery (ICA) thrombi. She underwent stent-retriever mechanical thrombectomy of bilateral ICA and cerebral venous sinuses. Next day she had right hemiparesis and expressive dysphasia, which are improving. Thromboses due to VITT can progress rapidly to involve cerebral arteries and venous sinuses, and may warrant urgent arterial and venous thrombectomy to reduce morbidity and mortality.